Broad-Spectrum Antibacterial Effects of Human Adipose-Derived Stromal Cells - Paul Monsarrat; Philippe Kémoun; Louis Casteilla; Valérie Planat-Bénard (Stem Cells International)
Introduction. Many pathological conditions may benefit from cell therapy using mesenchymal stromal cells, particularly from adipose tissue (ASCs). Cells may be grafted in an environment with a remnant polymicrobial component. The aim is to investigate the behavior of ASCs when brought in contact with a large panel of bacteria. Materials and Methods. Carboxyfluorescein-labelled bacterial interaction with ASCs was followed by confocal time-lapse microscopy. Costaining with LAMP-1 was also analyzed. Viability of 4 gram-negative and 4 gram-positive bacterial strains after 6 h of coculture with ASCs was assessed by agar colony counting and by flow cytometry using SYTO-62®/propidium iodide (PI) for membrane permeabilization and DiOC6 for depolarization. A murine model of periodontitis was used to assess in vivo antibacterial capacities of ASCs. Results. A significant increase of PI-positive events for all bacterial strains and an increase of the DiOC6 signal were obtained after contact with ASCs. The number of CFU was also significantly decreased for several bacterial strains. 0.4 μm transwell systems illustrated the necessary direct contact to induce maximal bacterial membrane damages. Some bacteria were observed into phagolysosomes, confirming macrophage-like properties of ASCs. In vivo, the bacterial load was significantly lower in the ASC-grafted side compared to the control. Conclusion. Our results highlight for the first time a broad range of antibacterial actions of ASCs, by phagocytosis, secretion of oxygenated free radicals and antibacterial molecules. These data are in line with the development of new therapeutic strategies based on ASC transplantation, appropriated in immune-dysbiotic tissue context such as periodontitis or chronic wounds.